STYLISTIC FEATURES OF COMPOUND SENTENCES IN ENGLISH AND UZBEK: COMPARATIVE ANALYSIS AND TRANSLATION ISSUES - Erdanova Zebiniso Abilkosimovna; Turg’unova Durdona (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article provides an in-depth comparative analysis of the syntactic structures and stylistic features of compound sentences in English and Uzbek languages. It explores how the differences in sentence construction impact stylistic expression and translation. The paper discusses common translation challenges faced when rendering compound sentences from English to Uzbek and offers strategies to preserve the original stylistic effects in the target language.